STUDI PENDAHULUAN : KEBERADAAN KURA-KURA ROTE (Chelodina mccordi, Rhodin 1994) DI PULAU ROTE, NUSA TENGGARA TIMUR - Wempy Endarwin; Adininggar Ul-Hasanah; Rodrigo Ibrrandi Vazquez; Mirza Dikari Kusrini (Department of Forest Resources Conservation and Ecotourism - IPB University, 2005)
A preliminary to investigate the remaining population of Rote snake-necked turtle Chelodina mccordi in Rote Island, Nusa Tenggara Timur was conducted in 20th of May – 25 th of June 2005. Based on previously known turtle distribution and interviews with local people, we surveyed 105 locations in Rote Island. We found 35 locations in Rote island suitable for turtle habitat, in which based on interviews 26 locations were previosly known as turtle habitats but no turtles were found anymore during the last few years, and nine locations where turtles are still occasionally seen. Our survey yielded no sighting of terrapin, we only found one snake-necked turtles brought by harvester from Peto marsh. Threats to Rote snake-necked turtles are hunting, loss of habitat to agricultural conversion and polution from agricultural land, and grazing by herds. More survey need to be carried out, especially during rainy season where there are more possibility of finding this turtle.Keywords: Rote, turtle, habitat, conservation, Indonesia; Chelodina mccordi